Coronado Hall main exponent of the documentary and bibliographic heritage of the Universidad Central "Marta Abreu" de Las Villas (Cuba) - Paz Enrique, Luis Ernesto (2024)
Francisco de Paula Coronado is a significant personality in 20th-century Cuban historiography and library science. Due to his outstanding work, he served as the director of the National Library "José Martí" from 1920 to 1946. Throughout his life, he devoted himself to collecting important bibliographic heritage works, including three incunabula and original manuscripts of universal history and Cuba. Due to various reasons, his library came under the custody of the Universidad Central "Marta Abreu" de Las Villas, where it is currently located. This gem of the bibliographic heritage is little known and therefore not frequently consulted by researchers and historians. This contribution aims to characterize the Coronado Collection based on the heritage values of the documents it preserves. The study was categorized as descriptive with a theoretical contribution. Classic documentary analysis was used as the main method. The history of the collection, composition of the holdings, and level of preservation were analyzed.